Conception and organization of a poison center - IRIMCA, Olga; STINCA, Kristina; CORETCHI, Roman; PINZARU, Iurie (One Health & Risk Management, 2023)
Introduction. Poison Center (PC) provides poison prevention and safety information, professional education, and assistance in diagnosing and treating poisoning incidents according to the monographs and database information. By addressing different types of poisonings, PCs save money and lives by reducing unnecessary healthcare expenses. PCs are accessible 24/7 and provide information or advice regarding actual or potential poisoning exposures. They also serve as a triage function by either providing information or referring calls to appropriate agencies. PCs have evolved a common set of activities to deal with these needs, primarily centered around telephone lines staffed by specialists with training in clinical toxicology, a wide range of consultants, and extensive collaborations with public health agencies. Aim. This study aims to assess the need for creating a PC in the Republic of Moldova and to develop its own organizational concept. Material and methods. The study involved visiting two PCs to understand their capacities and needs, which could serve as a model for the Republic of Moldova’s PC. Results. PCs operate 24/7, providing information related to poisonings and chemical agents to the public and healthcare professionals. They play a critical role in the prevention and management of poisonings. The benefits of PCs include accessible and affordable healthcare, reduced healthcare costs and unnecessary hospitalizations for mild and moderate poisonings, toxicological surveillance, public and professional education, and research on product safety and toxicity. PCs also reduce emergency department visits for poisonings and shorten hospital stays for poisoned patients. The services of a PC are provided free of charge to the caller. During the study visit to PCs in Estonia and Hungary, the researchers gained insight into their operations, including their databases on chemicals such as pesticides, industrial chemicals, consumer products, and other hazardous materials. The number of staff working in the centers varies depending on the volume of calls received. In Estonia, the staff employed at the PC have nursing qualification, while in Hungary, the staff includes biologists, chemists, and pharmacists. Poison control centers possess an efficient, real-time surveillance mechanism. During the study tour the main documents required for creating and managing a PC were presented, including the actors involved in ensuring its functionality and development, the availability and supply of antidotes, and the ability to respond quickly to incidents and chemical emergencies. Conclusions. The study tour of these successful models of PCs clearly demonstrated the need for the establishment of a PC in the Republic of Moldova. The first step is to assess the existing national capacities and develop a concept for the creation of a PC. It is important to note that PCs improve the efficiency of healthcare expenditure and contribute to the sustainability of the healthcare system. Investing in PCs leads to significant cost savings for the healthcare system while improving public health outcomes. Therefore, establishing a PC in the Republic of Moldova should be considered a valuable investment for the health of the public.